Endoplasmic reticulum stress promotes inflammation-mediated proteolytic activity at the ocular surface - Woodward, Ashley M. (Sci Rep, 2020)
A growing body of evidence implicates endoplasmic reticulum (ER) stress in the pathogenesis of chronic inflammatory and autoimmune disorders. Here, we demonstrate that the proinflammatory cytokine TNFα stimulates matrix metalloproteinase 9 (MMP9) at the ocular surface through a c-Fos-dependent mechanism of ER stress. We found positive reactivity of the molecular chaperone BiP/GRP78 in conjunctival epithelium of patients with ocular cicatricial pemphigoid and increased levels of BiP/GRP78, sXBP1 and GRP94 in human corneal epithelial cells treated with TNFα. Pharmacological blockade of ER stress in vitro using dexamethasone or the chemical chaperones TUDCA and 4PBA attenuated MMP9 expression and secretion in the presence of TNFα. Moreover, expression analysis of genes associated with inflammation and autoimmunity identified the c-Fos proto-oncogene as a mediator of ER stress responses in epithelial cells. Substantially less TNFα-induced MMP9 expression occurred when c-Fos signaling was suppressed with a function-blocking antibody. Taken together, these results indicate that activation of ER stress contributes to promote inflammation-mediated proteolytic activity and uncovers a target for restoring tissue homeostasis in ocular autoimmune disease.